СОВРЕМЕННЫЕ АСПЕКТЫ ПОВЫШЕНИЯ КОНКУРЕНТОСПОСОБНОСТИ ЭКОНОМИКИ КАЗАХСТАНА - Досымбекова, Г К (Journal of Economic Research & Business Administration, 2015)
In terms of entrance of Kazakhstan to the number of devoloped countries special novelty obtains questions of increasing the competitiveness of economy of the country. As the world experience shows, the devolopment of clustering the economy is one of the perspective directions for Kazakhstan. Problems of competitiveness of economy Kazakhstan and opportunities for using clustering are identified.